(3NhGU GdCMLGQ ef GdjhGbjJ hGdLhGgQs - (3YR GdOjf CHi ESMb EHQGgje Hf eMeO Hf Ydj Hf WQNGf GdCfUGQj GdShjOi,J (B690 (3g` s ((3eMeO CHj GdjSQ Hf CMeO TgGH Hf eMeO Hf CHj GdLhO GHf HQgGf GdOjf s)
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3aefg GdjGbhJ bGd CHh GdQjMGf (B: (3GdjGbhJ CQHYI CfhGY s
(3BNQgG (B:s
(3Je hVY TF ef GdaVI HYjOkG Yfg HYOO NeSI CPQY LPH GdaVI hdh cGfJ eSeQI hGddg CYde HGdUhGH s
(3Vef eLehY s
(3PcQJ GdeUGOQ deDda gPG GdcJGH GSeg cJGH HYfhGf(B" (3GdHGgQ ai NhGU GdLhGgQ (B" (3hdYdg gPG GdcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B650 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B40 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs